1996
DOI: 10.1017/s135772980002823x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fine grinding or sodium hydroxide treatment of wheat, offered as part of a concentrate supplement, on the performance of lactating dairy cows

Abstract: A study was conducted to examine the effect of fine grinding or sodium hydroxide treatment of wheat, and increasing concentrate food level, on milk production. Two concentrates based either on ground wheat (450 g/kg, GW) or sodium hydroxide treated wheat (500 g/kg, SW) were offered at four concentrate levels of 2-5, 5-0, 7-5 and 10-0 kg dry matter (DM) per day to 24 dairy cows in a three-period, change-over design experiment. On average, across all concentrate food levels, silage DM intake was significantly (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…These data support the principal that total tract digestibility of starch is related more to ruminal (Figure 8) digestion than intestinal digestion. In a study investigating the use of NaOH (3.5%> NaOH per kg DM) treated wheat grain vs ground wheat, Mayne and Doherty (1996) reported no difference in the apparent digestibility of dry matter (DM) or organic matter (OM) between the two treatments for dairy cows. These data suggest that NaOH treatment has less effect on digestibility when used to treat sorghum than with the treatment of wheat.…”
Section: Ruminal Starchmentioning
confidence: 99%
See 1 more Smart Citation
“…These data support the principal that total tract digestibility of starch is related more to ruminal (Figure 8) digestion than intestinal digestion. In a study investigating the use of NaOH (3.5%> NaOH per kg DM) treated wheat grain vs ground wheat, Mayne and Doherty (1996) reported no difference in the apparent digestibility of dry matter (DM) or organic matter (OM) between the two treatments for dairy cows. These data suggest that NaOH treatment has less effect on digestibility when used to treat sorghum than with the treatment of wheat.…”
Section: Ruminal Starchmentioning
confidence: 99%
“…Digestibility coefficients for wheat OM were 81% with both treatments (Mayne and Doherty, 1996). Krause et al (1998) determined the effects of the addition of fibrolytic enzymes to whole barley grain on digestion in four ruminally cannulated steers.…”
Section: Ruminal Starchmentioning
confidence: 99%
“…Mayne and Doherty (1996) neither found differences in the energy values of grass silage based diets with GW or NaW, incorporated in the concentrate. No literature data were found on the energy value of EnW, but Kennelly et al (1988) found a comparable energy value for ensiled rolled HMB and rolled dry barley.…”
Section: Nutritive Value Of the Feedstuffsmentioning
confidence: 67%
“…The data from literature on NaOH treated wheat (NaW) are also restricted and somewhat contradictive. Kung et al (1983) found negative effects of NaOH treated grain on the milking performance, whereas Sriskandarajah et al (1980) and Mayne and Doherty (1996) found higher milk yields and increased intake with NaW vs. rolled wheat (RW) and ground wheat (GW), respectively.…”
Section: Introductionmentioning
confidence: 99%